Conditions of Coral Reef in Bunaken Island North Sulawesi Province - Alex Denny Kambey (Jurnal Ilmiah PLATAX, 2014)
Community structure of corals were analyzed to understand their response to different conditions of coral reefs in several places of Bunaken island. This study focused on species abundance and diversity including Shannon-Wiener’s species diversity (H’) respectively. The result recorded 67 species and 29 genera of corals. In general, the condition of coral reefs in Bunaken Island in good condition.   Keywords: Community structure, coral reef.   A B S T R A K   Struktur komunitas karang dianalisis untuk memahami respon   terhadap perbedaan kondisi  terumbu karang di beberapa tempat pulau Bunaken. Penelitian ini difokuskan pada kelimpahan dan keragaman spesies termasuk keragaman Shannon-Wiener spesies (H') masing-masing. Hasilnya mencatat 67 spesies dan 29 genera karang. Secara umum, kondisi terumbu karang di Pulau Bunaken dalam kondisi baik.   Kata kunci : Komunitas struktur, terumbu karang.